Evaluation of Properties of Stone Mastic Asphalt Slab Produced Using a New Rotary Compactor - Pourtahmasb, Mohammad Saeed (2009)
Recent laboratory studies have shown that the compaction can highly affect the performance of Stone Mastic Asphalt (SMA) mixtures. California kneading compactors, Gyratory compactors and Marshall impact compactors are being used as SMA compactors in the mix design methods. But according to the performance of the SMA compacted specimens, none of them could simulate the field compaction one hundred percent. Breaking down of the aggregates during compaction is one of the most extensive problems in road mixtures and if that becomes prevalent, the mixture may not meet the minimum VMA (void in mineral aggregate) and VCA (void in coarse aggregate) requirements. In this study, the newly developed Rotary compactor was introduced as a new equipment for laboratory compaction to reduce the previous laboratory compactor problems and to have better field simulation. Physical properties of materials such as aggregates, bitumen and fiber have been considered as one of the objectives in this research. So the physical properties of the asphalt mixture materials were determined in accordance with relevant international standards such as ASTM, AASHTO and BS. The weight of required materials per each Rotary slab was approximately130kg and Marshall mix design was selected as a mix design method to measure the Optimum Asphalt Content (OAC) and based on the Asphalt Institute method the OAC was obtained 6%. A total of three SMA slabs were prepared in accordance with UPM inhouse protocol for Rotary compactor and 88 core specimens with 100mm diameters and 8 core specimens with 200mm diameter were cored out and subjected to performance tests. SMA core specimens with 100mm diameters were tested for density, air void, stability, flow, resilient modulus, indirect tensile strength (IDT), moisture induced damage and fatigue. Also, 8 core specimens with 200mm diameters were subjected to Loaded Wheel Tracking (LWT) test to measure the rut resistance level of the Rotary SMA specimens. Finally, the performance test results were tabulated and analyzed. The entire analysis indicated that the results can be accepted in terms of performance of the SMA core specimens compacted using the newly developed Rotary compactor. It can be concluded that Rotary compactor can be used as a new heavy duty laboratory compactor.